2023
DOI: 10.1021/acssuschemeng.2c05759
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research Advancements in Catalytic Pyrolysis of Plastic Waste

Abstract: The disposal of plastic waste is currently one of the major global issues affecting environmental balance and mankind. It is therefore crucial to turn waste plastic into value-added products. Thermochemical recycling techniques have been researched extensively to generate fuels, monomers, and other value-added products. It has been determined that pyrolysis is an effective method for chemical recycling. Plastic wastes are transformed into products including liquid oil, gas, and solid residues during the therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 154 publications
0
9
0
Order By: Relevance
“…Additionally, the techno-economic viability of catalytic pyrolysis of plastic waste has been demonstrated, provided that the plastic refuse prices remain low, especially for plants having high operational capacity. 16 Plastic cracking with acid catalysts follows a carbocationic mechanism. It usually proceeds in the initial reaction steps via carbenium ions produced by the abstraction of a hydride ion (Lewis acid sites) from the polymer or by the addition of a proton (Brønsted acid sites) to the polymer forming a carbonium ion.…”
Section: Catalytic Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the techno-economic viability of catalytic pyrolysis of plastic waste has been demonstrated, provided that the plastic refuse prices remain low, especially for plants having high operational capacity. 16 Plastic cracking with acid catalysts follows a carbocationic mechanism. It usually proceeds in the initial reaction steps via carbenium ions produced by the abstraction of a hydride ion (Lewis acid sites) from the polymer or by the addition of a proton (Brønsted acid sites) to the polymer forming a carbonium ion.…”
Section: Catalytic Pyrolysismentioning
confidence: 99%
“…Additionally, the techno-economic viability of catalytic pyrolysis of plastic waste has been demonstrated, provided that the plastic refuse prices remain low, especially for plants having high operational capacity. 16…”
Section: Thermal and Catalytic Pyrolysis Of Plastic Wastementioning
confidence: 99%
See 1 more Smart Citation
“…[2] Pyrolysis is one of the most conventional routes to this target, usually operated at 500-600 °C. [3] However, such harsh condition leads to enormous energy consumption and the rapid deactivation of catalysts. [4] As an alternative way, hydro-genolysis over monofunctional metal catalysts can take place at a relatively low temperature of 300 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Chari et al 20 calculated the climate change impact of −371 kg CO 2 per ton of mixed plastic wastes processed by hydrogen production process. Mishra et al 21 systematically summarized the effect of different catalysts on product composition and yield when thermo-catalyzing waste plastics, starting from techno-economic evaluation, utilization of byproducts, utilization as fuel, and kinetic studies of feedstock pyrolysis. From their results, it can be found that a catalytic pyrolysis system for plastic wastes is indeed low cost, environmentally friendly, and efficient.…”
mentioning
confidence: 99%